Statebuilding in the Central African Republic : the preeminence of the Economic Community of Central African States in the ‘transition’ process between 2012-2016 - (:unkn) unknown (My University, 2019)
Since its independence in 1960, the Central African Republic (CAR) has oscillated between turmoil and moments of relative stability, notably under the military regimes of Jean-Bedel Bokassa and André Kolingba. The country’s quasi chronic political instability since the end of the 1980s, has led to successive international responses in the form of peace missions starting in 1997 and ultimately aimed at statebuilding as a solution to the CAR’s crisis of the political. The outbreak of an armed conflict at the end of 2012 led by the Seleka rebellion, however, underlines the weakness of this international enterprise, which ignores the internal political and social dynamics of ‘recipient’ societies. This violent resumption of hostilities in the CAR also brings to the fore the question of the rigidity of the concept of the state and its universal relevance, as limits of international statebuilding policies. The multitude of local and international actors operating in the CAR is indicative of the complexity of this conflict and renders the possibility of a lasting solution difficult. The primary role of the Economic Community of Central African States (ECCAS) in the statebuilding in CAR between 2012 and 2016 is a manifestation of the struggle for influence that this regional actor - in this case its member states - won. The ‘victory’ of ECCAS was gained at the expense of an objective and viable solution to the Central African question, ‘for the benefit’ of states such as Chad and France, and individuals such as Idriss Deby and Denis Sassou Nguesso. The success of this ‘diplomacy of conspiracy’ is illustrative of power dynamics and power struggle and the convergence of political regimes in the subregion, as well as the very paradoxical relationship that France has with its former colonies.
Keywords: African Research